Exploring Postpartum Depression among Palestinian Women in Genocide: A Feminist Perspective on Social Support and Health Access in Gaza - Baraka Abusafia (22391770) (2025)
This study examines the prevalence of postpartum depression among 209 Palestinian women in Gaza, aged 18 to 45 years, living under the compounded stresses of genocide, displacement, and socioeconomic hardship. Using a feminist lens, the research explores how perceived social support impacts depression levels in this marginalized population. Data were collected through validated tools, including the Multidimensional Scale of Perceived Social Support (MSPSS) and the Edinburgh Postnatal Depression Scale (EPDS). Results reveal that 85.65% of participants exhibited symptoms of probable postpartum depression, with key predictors including younger age, economic hardship, family loss due to ongoing genocide, and exposure to trauma. The findings underscore the protective role of social support and call for feminist-informed, community-based interventions to address the unique needs of displaced women in conflict zones. This study contributes to feminist social work by advocating for sustainable support networks to promote resilience and well-being in conflict-affected populations. Other Information Published in: Affilia License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1177/08861099251387632